Peningkatan Kapasitas Kelompok Pembudidaya Ikan Kumis Jaya melalui Pelatihan Formulasi Bahan Pakan Alternatif Lele - Anisah Nasution; Mudastsir; Rahmawati (Jurnal Pemberdayaan Masyarakat, 2025)
This community service program aims to enhance the capacity of the Fish Farmers Group (POKDAKAN) Kumis Jaya in independently formulating catfish feed. The main problems faced by the partner are their dependence on expensive commercial feed and limited knowledge about fish nutritional needs, particularly the ideal protein content. These issues result in high production costs and suboptimal fish growth. The activities included delivering material on catfish nutritional requirements, introducing locally available feed ingredients, and providing training on feed formulation using the Pearson Square method. A participatory approach was applied to ensure that group members actively understood the basic concepts while also practicing formulation calculations. The evaluation results showed a significant increase of 75% in participants’ understanding. They recognized the importance of 25–30% protein content in feed to support healthy catfish growth and were able to calculate feed formulations independently using local ingredients. This activity successfully improved the independence of Kumis Jaya in feed formulation, while also providing opportunities to reduce production costs and strengthen the sustainability of catfish farming.